Cinema and Reverberation: Zama, Montage and History - Villalobos Ruminott, Sergio Roberto (Revista de Historia Social y de las Mentalidades, 2023)
Through a critical reading of Lucrecia Martel’s fourth film, Zama (2017), based on Antonio di Benedetto’s homonymous novel (1956), we elaborate a reflection on the relationship between cinema and history, highlighting the strategies used by the Argentine director in the making of her work. We maintain that, beyond a merely instrumental and illustrative use of cinema, Martel allows us to think of cinematographic montage as a way of denarrativizing and demonumentalizing the conventional narrative of history, thereby opening a relationship with the past, freed from the historicist logic that seems to characterize both the documentary genre and political cinema in general. In this sense, the question of history and its reverberations appears in Zama as elements that complicate the conventional relationship between cinema and politics.